2009
DOI: 10.1038/sj.bjc.6605452
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of TOPK stratified by KRAS and BRAF gene alterations in sporadic, hereditary and metastatic colorectal cancer patients

Abstract: BACKGROUND: Our aim was to investigate the prognostic and predictive value of the oncogenic MAPKK-like protein T-cell-originated protein kinase (TOPK) stratified by KRAS and BRAF mutations in patients with sporadic, hereditary and metastatic colorectal cancer (CRC) treated with anti-EGFR therapy. METHODS: Immunohistochemistry (IHC) for TOPK was performed on four study groups. Group 1 included two subgroups of 543 and 501 sporadic CRC patients used to test the reliability of TOPK expression by IHC. In Group 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 41 publications
(39 reference statements)
1
51
0
Order By: Relevance
“…These observations are partly consistent with the primary findings that patients with TOPK overexpression had a significantly poorer prognosis in stage I lung adenocarcinoma [16]. Zlobec and colleagues [18] also found that TOPK was a valuable prognostic factor in colorectal cancer.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These observations are partly consistent with the primary findings that patients with TOPK overexpression had a significantly poorer prognosis in stage I lung adenocarcinoma [16]. Zlobec and colleagues [18] also found that TOPK was a valuable prognostic factor in colorectal cancer.…”
Section: Discussionsupporting
confidence: 58%
“…For example, TOPK is involved with highly proliferative cells and tissues and is highly expressed in many types of tumors such as lymphoma, leukemia, breast cancer, Ewing sarcoma, and colorectal cancer [6][7][8][9][10]. High TOPK expression can promote cell proliferation [11][12][13] and prevent apoptosis [14,15] and is associated with a poor prognosis [16][17][18][19]. Moreover, TOPK expression may play an important role in the progress of cytokinesis and inflammation [20][21][22].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Zlobec et al (2010) showed that expression of TOPK, in combination with KRAS and/or BRAF mutations, is linked to an unfavorable prognosis in sporadic colorectal cancer. In this study, we also found that high expression of TOPK is significantly associated with advanced stage and lymph node involvement (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The KRAS gene mutation-positive rate reported outside Japan is 30 -40% (13). When comparing data from overseas, or when discussing the relationship between background primary factors and mutation-positive rate, it is necessary to keep the positive-rate measurement error to within a fixed range.…”
Section: Endpoints and Sample Sizementioning
confidence: 99%